The Effect of Ciprofloxacin on Prostate-Specific Antigen (PSA) - Andre Dwi Gustiano; Alvarino Alvarino; Etriyel MYH; Peri Eriad Yunir (International Journal Labs, 2022)
Increased PSA levels can be caused by prostate cancer, prostate infection, and BPH. Several studies report that the use of antibiotics can affect PSA levels. This study aims to determine the effect of ciprofloxacin administration in patients with prostate-specific antigen values ??of 4-10 ng/mL. This was an analytical study with a prospective cohort design. This study was conducted at Dr. M. Djamil Hospital, Padang starting from July 2022 until October 2022. The sampling technique used non-probability sampling with consecutive sampling method. The patient was given the antibiotic ciprofloxacin 2x500 mg for 2 weeks. PSA measurements were carried out before and after administration of antibiotics. There were 20 subject with an average age of 62.65 years (52-79). The mean of initial PSA value was 6.53 ng/mL and the final PSA value was 5.76 ng/mL. There was a significant difference between PSA levels before and after administration of ciprofloxacin (p=0.000). The use of antibiotics in patients with PSA levels of 4-10 ng/ml can reduce PSA levels.